Advancement In Oocyte Collection and Preservation - Sarwan, Jyoti; Abdalmajed, Mohamed; Alhaj, Mohamed; Rehman, Aisha; Borgohain, Seme; Simran, Simran; Tasleem, Tasleem; Kaur, Dipneet (Journal of Neonatal Surgery, 2025)
Vitrification has become a prevalent and effective technique for cryopreservation in the field of reproductive biology. Recent findings indicate that this method is not only reliable but also serves as a highly efficient means for storing human oocytes at low temperatures. The latest techniques, when paired with the right selection of cryoprotectants, tools, and methods, along with optimized conditions, can achieve nearly 100% morphological survival rates. By standardizing this technique and addressing biosafety concerns while preserving its advantages, vitrification could be integrated into the routine practices of human embryo laboratories. This could provide a viable therapeutic option in various biological and social situations, as well as in addressing common logistical challenges currently encountered. Ovulation induction (OI) is a cornerstone of infertility treatment, particularly for anovulatory women, accounting for a significant proportion of female infertility cases. This review studies the body’s processes that cause ovulation via the hypothalamic-pituitary-ovarian axis and provides information on common medical drugs used for ovulation induction. Both traditional agents such as Clomiphene Citrate and Letrozole, gonadotropins and hCG are discussed together with newer treatments that include kisspeptin analogs and SERMs. Laser-assisted hatching improved IVF. At Dr. Shobha’s Fertility Center, Muktsar Sahib Punjab conducted the study from July 2024, to December 2024. The study included 80 ICSI-treated infertile couples. Women aged 20-30 and 30-40 were tested utilizing laser exposure. A noncontact RI-SATURN V laser was employed for zona pellucida manipulation. All participants had hormone tests, transvaginal ultrasounds, and hysteroscopy or laparoscopy done during treatment cycle. Fixed and extended ovarian hyperstimulation treatments were used. IVF success rates vary by age, with 30-40 having 83%, 20-30 (84%). The laser exposure hatching had the highest success rate (92%), and the lowest success rate (48%). A significant positive correlation was established between laser exposure and clinical pregnancy outcomes. The study reveals age, especially 30-40, may impair IVF success. Additionally, a laser exposure hatching increases IVF success rates. The recommended laser exposure period for all age groups is 4.5 µs, with younger women recommended at 2 µs and older women at 8 µs. Laser-assisted hatching methods, specifically diode laser exposure periods, were evaluated for in vitro fertilization success. The study evaluated how age influences IVF couples' clinical pregnancy outcomes. The findings optimize laser parameters for assisted reproductive technology